Understanding pre-university students’ learning styles and motivation during online environment - Nur Alia Yasmin Mohd Nizam,; Nur Aina Nabila Norazizi,; Nurul Aina Kasman,; Nurin Atilia Putri Nazaruddin,; Faieza Samat,; Tengku Elmi Azlina Tengku Muda, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Transition from in-person to online learning had impacted students in the way they learn. The aim of this research is to understand how the online environment had influenced pre-university students’ learning styles and motivation. The objectives are to determine the learning styles practiced by the students and their level of motivation during the online environment. Two sets of questionnaires were distributed online to 315 ASASIpintar pre-university students of Universiti Kebangsaan Malaysia. The prolonged Movement Control Order (MCO) imposed by the country had caused ASASIpintar students to be in a long-term online environment, nevertheless the results reveal that the students had a high level of motivation while most of them were visual learners. Moreover, there is a positive very weak correlation between visual learning styles and motivation. Hence, the online environment had influenced students’ preferences of learning styles in which learning by reading or seeing pictures seemed to be the most appropriate way to learn in this environment. Visual learning styles had led to an increase in students’ motivation for learning.